2018
DOI: 10.3928/01477447-20180815-04
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Injury Following Interscalene Blocks: A Systematic Review to Guide Orthopedic Surgeons

Abstract: The purpose of this review was to determine the incidence and duration of peripheral neurologic symptoms following interscalene blocks for shoulder surgery. Three databases were reviewed for subjective and objective injuries by guidance modality and delivery method. The incidence of neurologic injuries following single site injection interscalene blocks, 3.16%, was significantly less than the 5.24% incidence for continuous catheter infusion interscalene blocks. Less than 0.51% of peripheral neurologic symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…The use of anesthetics relieves discomfort in patients during operation, but extensive application of anesthetics can cause damage to the nervous system. However, increasing evidence has shown that excessive use of anesthetics can lead to damage in the nervous system (Holbrook & Parker, 2018; Kitagawa et al., 2004). Isoflurane is a traditional anesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…The use of anesthetics relieves discomfort in patients during operation, but extensive application of anesthetics can cause damage to the nervous system. However, increasing evidence has shown that excessive use of anesthetics can lead to damage in the nervous system (Holbrook & Parker, 2018; Kitagawa et al., 2004). Isoflurane is a traditional anesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were excluded if RA was administered via a continuous catheter infusion (vs injected boluses), as the use of catheters in brachial plexus blockade has been associated with a higher incidence of neurologic injuries. 22 Finally, studies were excluded if RA was performed in the emergency department or if surgery was performed outside the operating room, because of the unique challenges of those environments.…”
Section: Methodsmentioning
confidence: 99%
“…116 Studies estimate that the frequency of nerve injuries can be as high as 3% to 5%, with the highest incidence associated with upper extremity interscalene blocks. 59 As orthopaedic surgeons are responsible for their patients' overall care, knowledge of these pain control strategies is imperative. The following review outlines the most commonly used PNBs that are currently available for both hip and knee arthroscopic procedures to better inform our sports medicine community in the fight to decrease opioid use after surgery.…”
mentioning
confidence: 99%
“…116 Studies estimate that the frequency of nerve injuries can be as high as 3% to 5%, with the highest incidence associated with upper extremity interscalene blocks. 59…”
mentioning
confidence: 99%